Realistic Mathematics Engineering for improving elementary school students’ mathematical literacy - Nurmasari, Linda; Budiyono; Nurkamto, Joko; Ramli, Murni (Journal on Mathematics Education, 2024)
Mastery of mathematical literacy is essential for developing life skills in the 21st century. Mathematical literacy is even more critical in elementary schools as it forms the basis for mastery at the junior and senior high school levels. Elementary school students differ in their characteristics from students at the higher education level. They, therefore, require an appropriate learning model to improve their mathematical literacy. This research aims to develop a learning model, termed Realistic Mathematics Engineering (RMEng), that combines the Realistic Mathematics Education approach with the steps of the Engineering Design Process and determines the model’s effectiveness. The model was validated by seven experts from three universities in Indonesia and had an Aiken validity index value of 0.786, indicating that it was valid. The RMEng model contains the following steps: understanding realistic problems, solving problems in informal ways, developing formal mathematics, developing products, and drilling. Discussions and presentations can be incorporated into each of these five steps. The RMEng model was subjected to the stages of preliminary and main field testing and was revised based on the suggestions of teachers and observers. Through experimental research compared to a control group, the RMEng model was proven more effective in increasing elementary school students’ mathematical literacy at the 0.000 significance level.